Anti-biological attachment material and preparation method thereof and anti-biological attachment float
By optimizing the polymer material formula and combining nano zinc oxide and other components, an anti-biological attachment floating material for offshore photovoltaic power generation was developed, which solved the problems of reduced bearing capacity and aging of floating bodies caused by biological adhesion in offshore photovoltaic power generation systems, and achieved the effect of long-term anti-biological attachment and extended floating body life.
Patent Information
- Application Number
- CN202310283374.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-03-20
AI Technical Summary
In offshore photovoltaic power generation systems, defiled organisms adhere to and grow on the surface of the floating body, resulting in a decrease in bearing capacity, low manual cleaning efficiency and high cost, and frequent cleaning will damage the floating body and shorten its service life.
Develop a bioadhesive material to optimize the raw material formula of polymer materials, combine nano zinc oxide, 2-(methoxycarbamoyl)benzimidazole, zinc pyrithione, hydrophobic white carbon black and copper ion fibers and other components to prepare floating materials with good bioadhesive properties.
It has achieved long-term effective prevention of biological adhesion, reduced the need for manual cleaning of floating bodies, thereby avoiding the negative impact of frequent cleaning on floating bodies, extending the service life of floating bodies, and is suitable for offshore photovoltaic power generation systems.
Smart Images

Figure BDA0004139254900000011 
Figure BDA0004139254900000022 
Figure BDA0004139254900000031
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to an anti-biological attachment material and a preparation method thereof and an anti-biological attachment float. Background Art
[0002] Offshore photovoltaic power generation is a new energy utilization method and resource development model, with the characteristics of high power generation, less land occupation, and easy integration with other industries. Due to the vast ocean area, offshore photovoltaic power generation has sufficient potential. However, the marine water environment is complex, and fouling organisms will attach and grow on the surface of offshore photovoltaic floats, resulting in a decrease in the carrying capacity of the floats. The maintenance method of manual cleaning is inefficient and costly, and is not suitable for large-scale photovoltaic power generation systems. In addition, manual cleaning will damage the surface of the float, accelerate the aging of the float, increase the tendency to crack, and affect the service life of the float.
[0003] Therefore, developing a floating material for offshore photovoltaic power generation that can effectively prevent biological attachment for a long time is an urgent problem to be solved in this field. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide an anti-biological attachment material and a preparation method thereof and an anti-biological attachment float. The material provided by the present invention has good anti-biological attachment performance, can effectively prevent biological attachment for a long time, and has good application prospects in the field of floating materials for offshore photovoltaic power generation.
[0005] The present invention provides an anti-biological attachment material, wherein the raw materials for its preparation include, by weight:
[0006]
[0007]
[0008] Preferably, the polymer base material includes high-density polyethylene and polyolefin thermoplastic elastomer.
[0009] Preferably, the melt flow rate of the high-density polyethylene at 190°C and 2.16 kg load is 10 to 20 g / 10 min; the environmental stress cracking time F of the high-density polyethylene at 50°C and 10% Igepal is 50 is ≥2000h; the Mooney viscosity ML(1+4) 121°C of the polyolefin thermoplastic elastomer is ≤20MU; the tear strength of the polyolefin thermoplastic elastomer is ≥25kN / m; and the glass transition temperature of the polyolefin thermoplastic elastomer is ≤-55°C.
[0010] Preferably, the particle size of the nano zinc oxide is 5 to 20 nm.
[0011] Preferably, the specific surface area of the hydrophobic white carbon black is 300 to 500 m 2 / g; the water contact angle of the hydrophobic silica is ≥150°.
[0012] Preferably, the matrix material of the copper ion fiber is one or more of polyethylene terephthalate, polyamide and polyetheretherketone; the copper content in the copper ion fiber is 5000-50000 ppm; the diameter of the copper ion fiber is 0.5-10 μm; and the aspect ratio of the copper ion fiber is ≥100.
[0013] Preferably, the auxiliary agent includes one or more of a coupling agent, a dispersant, an antioxidant and a weathering agent.
[0014] Preferably, in parts by weight, the raw materials for preparation include:
[0015]
[0016] The present invention provides a method for preparing the anti-biological attachment material described in the above technical solution, comprising the following steps:
[0017] The prepared raw materials are melt-blended and extruded to obtain the anti-biological attachment material.
[0018] The present invention provides an anti-biological attachment floating body, the surface material of the anti-biological attachment floating body is the anti-biological attachment material described in the above technical solution.
[0019] Compared with the prior art, the present invention provides an anti-biological attachment material and a preparation method thereof and an anti-biological attachment float. In terms of weight, the raw materials for preparing the anti-biological attachment material provided by the present invention include: 70 to 100 parts of polymer base material, 0.5 to 5.0 parts of nano zinc oxide, 0.5 to 3.0 parts of 2-(methoxycarbamoyl)benzimidazole, 0.5 to 3.0 parts of zinc pyrithione, 0.5 to 3.0 parts of hydrophobic white carbon black, 5 to 15 parts of copper ion fiber, and 0.6 to 4.0 parts of additives. The present invention optimizes the raw material formula of the polymer material to obtain a material with good anti-biological attachment ability, which can effectively prevent biological attachment for a long time; when the material is used as a floating material, it can effectively reduce the manual cleaning of the floating surface, thereby avoiding the negative impact of frequent manual cleaning on the floating body, and has good application prospects in the field of floating materials for offshore photovoltaic power generation. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] The present invention provides an anti-biological attachment material, wherein the raw materials for its preparation include, by weight:
[0022]
[0023] In the anti-biological attachment material provided by the present invention, the polymer base material preferably includes high-density polyethylene and polyolefin thermoplastic elastomer. Wherein, the melt flow rate (190°C, load 2.16kg) of the high-density polyethylene is preferably 10 to 20g / 10min, specifically 10g / 10min, 11g / 10min, 12g / 10min, 13g / 10min, 14g / 10min, 15g / 10min, 16g / 10min, 17g / 10min, 18g / 10min, 19g / 10min or 20g / 10min; the environmental stress cracking time F of the high-density polyethylene is preferably 10 to 20g / 10min, 11g / 10min, 12g / 10min, 13g / 10min, 14g / 10min, 15g / 10min, 16g / 10min, 17g / 10min, 18g / 10min, 19g / 10min or 20g / 10min; 50 (50°C, 10% Igepal) is preferably ≥2000h, more preferably 2000-8000h, specifically 2000h, 2500h, 3000h, 3500h, 4000h, 4500h, 5000h, 5500h, 6000h, 6500h, 7000h, 7500h or 8000h.
[0024] In the anti-biological attachment material provided by the present invention, in the polymer base material, the polyolefin thermoplastic elastomer has the advantages of high elasticity of rubber and easy processing of plastic, has good compatibility with polyolefins, has good tolerance for inorganic fillers, and has good toughening and modification effects on materials such as polyethylene. In the present invention, the Mooney viscosity ML (1+4) 121°C of the polyolefin thermoplastic elastomer is preferably ≤20MU, specifically 10MU, 11MU, 12MU, 13MU, 14MU, 15MU, 16MU, 17MU, 18MU, 19MU or 20MU; the tear strength of the polyolefin thermoplastic elastomer is preferably ≥25kN / m, more preferably 25 to 40kN / m, specifically 25kN / m, 26kN / m, 27kN / m, 28kN / m, 29kN / The glass transition temperature of the polyolefin thermoplastic elastomer is preferably ≤-55°C, more preferably -55 to -65°C, specifically -55°C, -56°C, -57°C, -58°C, -59°C, -60°C, -61°C, -62°C, -63°C, -64°C or -65°C.
[0025] In the anti-biological attachment material provided by the present invention, the content of the polymer base material in the preparation raw material can specifically be 70 parts by weight, 71 parts by weight, 72 parts by weight, 73 parts by weight, 74 parts by weight, 75 parts by weight, 76 parts by weight, 77 parts by weight, 78 parts by weight, 79 parts by weight, 80 parts by weight, 81 parts by weight, 82 parts by weight, 83 parts by weight, 84 parts by weight, 85 parts by weight, 86 parts by weight, 87 parts by weight, 88 parts by weight, 89 parts by weight, 90 parts by weight, 91 parts by weight, 92 parts by weight, 93 parts by weight, 94 parts by weight, 95 parts by weight, 96 parts by weight, 97 parts by weight, 98 parts by weight, 99 parts by weight or 100 parts by weight.
[0026] In the anti-biological attachment material provided by the present invention, for the embodiment in which the polymer base material includes high-density polyethylene and a polyolefin thermoplastic elastomer, the content of the high-density polyethylene in the preparation raw material is preferably 60 to 75 parts by weight, specifically 60 parts by weight, 60.9 parts by weight, 61 parts by weight, 62 parts by weight, 63 parts by weight, 64 parts by weight, 65 parts by weight, 66 parts by weight, 67 parts by weight, 68 parts by weight, 69 parts by weight, 70 parts by weight, 71 parts by weight, 72 parts by weight, 73 parts by weight, 74 parts by weight or 75 parts by weight; the content of the polyolefin thermoplastic elastomer in the preparation raw material is preferably 10 to 25 parts by weight, specifically 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight or 25 parts by weight.
[0027] In the anti-biological attachment material provided by the present invention, the nano zinc oxide is an inorganic antibacterial component, which can decompose negatively charged electrons in water and air under the irradiation of sunlight, especially ultraviolet light, and leave positively charged holes. Such holes can stimulate oxygen in the air to become active oxygen, and react with a variety of microorganisms to produce oxidation reactions, thereby playing a bactericidal role; in addition, zinc ions will gradually become free, and when it comes into contact with bacteria, it will combine with active proteases in the bacteria to make them inactive, thereby killing the bacteria, which can enhance the long-term anti-biological attachment effect of the material. In the present invention, the particle size of the nano zinc oxide is preferably 5 to 20 nm, specifically 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm or 20 nm.
[0028] In the anti-biological attachment material provided by the present invention, the content of the nano zinc oxide in the preparation raw material can be specifically 0.5 weight parts, 0.7 weight parts, 1 weight parts, 1.2 weight parts, 1.5 weight parts, 1.7 weight parts, 2 weight parts, 2.3 weight parts, 2.5 weight parts, 2.7 weight parts, 3 weight parts, 3.2 weight parts, 3.5 weight parts, 3.7 weight parts, 4 weight parts, 4.2 weight parts, 4.5 weight parts, 4.7 weight parts or 5 weight parts.
[0029] In the anti-biological attachment material provided by the present invention, the 2-(methoxycarbamoyl)benzimidazole (CAS No. 10605-21-7), also known as carbendazim, is a broad-spectrum fungicide, a highly effective and low-toxic systemic fungicide, and has a preventive and therapeutic effect on diseases caused by fungi (such as Ascomycetes and Polyascomycetes), interferes with the formation of spindles in mitosis of pathogens, affects cell division, and plays a bactericidal role. Its structural formula is shown below:
[0030]
[0031] In the anti-biological attachment material provided by the present invention, the content of the 2-(methoxycarbamoyl)benzimidazole in the preparation raw materials can specifically be 0.5 weight parts, 0.6 weight parts, 0.7 weight parts, 0.8 weight parts, 0.9 weight parts, 1 weight part, 1.1 weight parts, 1.2 weight parts, 1.3 weight parts, 1.4 weight parts, 1.5 weight parts, 1.6 weight parts, 1.7 weight parts, 1.8 weight parts, 1.9 weight parts, 2 weight parts, 2.1 weight parts, 2.2 weight parts, 2.3 weight parts, 2.4 weight parts, 2.5 weight parts, 2.6 weight parts, 2.7 weight parts, 2.8 weight parts, 2.9 weight parts or 3 weight parts.
[0032] In the anti-biological attachment material provided by the present invention, the zinc pyrithione (CAS No. 13463-41-7) is a coordination complex of zinc and pyrithione, which can inhibit the growth of Gram-positive and Gram-negative bacteria and molds and has a strong antifungal effect. Its structural formula is as follows:
[0033]
[0034] In the anti-biological attachment material provided by the present invention, the content of the zinc pyrithione in the preparation raw material can be specifically 0.5 weight parts, 0.6 weight parts, 0.7 weight parts, 0.8 weight parts, 0.9 weight parts, 1 weight part, 1.1 weight parts, 1.2 weight parts, 1.3 weight parts, 1.4 weight parts, 1.5 weight parts, 1.6 weight parts, 1.7 weight parts, 1.8 weight parts, 1.9 weight parts, 2 weight parts, 2.1 weight parts, 2.2 weight parts, 2.3 weight parts, 2.4 weight parts, 2.5 weight parts, 2.6 weight parts, 2.7 weight parts, 2.8 weight parts, 2.9 weight parts or 3 weight parts.
[0035] In the anti-biological attachment material provided by the present invention, the hydrophobic white carbon black is a porous substance whose composition can be represented by SiO2·nH2O, which has a large specific surface area, strong adsorption capacity, and extremely strong hydrophobicity. Mixing it with the organic antibacterial component can make the functional additive fully adsorbed in the surface wrinkles and internal pores of the super-hydrophobic white carbon black, which can improve the dispersibility of the functional additive, so that the functional additive can fully exert its functionality in the matrix. At the same time, the three-dimensional network structure has an adjustable sustained release function for the functional additive, which can effectively improve the anti-biological attachment ability. In the present invention, the specific surface area of the hydrophobic white carbon black is preferably 300 to 500 m 2 / g, specifically 300m 2 / g, 310m 2 / g, 320m 2 / g, 330m 2 / g, 340m 2 / g, 350m 2 / g, 360m 2 / g, 370m 2 / g、380m 2 / g, 390m 2 / g, 400m 2 / g, 410m 2 / g, 420m 2 / g, 430m 2 / g, 440m 2 / g, 450m 2 / g, 460m 2 / g, 470m 2 / g, 480m 2 / g, 490m 2 / g or 500m 2 / g; the water contact angle of the hydrophobic silica is preferably ≥150°, more preferably 150°-170°, specifically 150°, 151°, 152°, 153°, 154°, 155°, 156°, 157°, 158°, 159°, 160°, 161°, 162°, 163°, 164°, 165°, 166°, 167°, 168°, 169° or 170°.
[0036] In the anti-biological attachment material provided by the present invention, the content of the hydrophobic white carbon black in the preparation raw material can specifically be 0.5 weight parts, 0.6 weight parts, 0.7 weight parts, 0.8 weight parts, 0.9 weight parts, 1 weight part, 1.1 weight parts, 1.2 weight parts, 1.3 weight parts, 1.4 weight parts, 1.5 weight parts, 1.6 weight parts, 1.7 weight parts, 1.8 weight parts, 1.9 weight parts, 2 weight parts, 2.1 weight parts, 2.2 weight parts, 2.3 weight parts, 2.4 weight parts, 2.5 weight parts, 2.6 weight parts, 2.7 weight parts, 2.8 weight parts, 2.9 weight parts or 3 weight parts.
[0037] In the anti-biological attachment material provided by the present invention, the copper ion fiber is a synthetic fiber containing copper element, has good antibacterial effect, high safety, does not produce drug resistance, and has excellent mechanical properties, heat resistance and chemical stability. In the present invention, the base material of the copper ion fiber is preferably one or more of polyethylene terephthalate, polyamide and polyetheretherketone; the copper content in the copper ion fiber is preferably 5000-50000ppm, specifically 5000ppm, 10000ppm, 15000ppm, 20000ppm, 25000ppm, 30000ppm, 35000ppm, 40000ppm, 45000ppm or 50000ppm; the diameter of the copper ion fiber is preferably 0.5-10μm, specifically 0.5μm, 1μm, 1.5μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm m, 8μm, 9μm or 10μm; the aspect ratio of the copper ion fiber is preferably ≥100, more preferably 100-200, specifically 100, 110, 120, 130, 140, 150, 160, 170, 180, 190 or 200; the tensile strength of the copper ion fiber is preferably 600-900MPa, specifically 600MPa, 620MPa, 640MPa, 660MPa, 680MPa, 700MPa, 720MPa, 740MPa, 760MPa, 780MPa, 800MPa, 820MPa, 840MPa, 860MPa, 880MPa or 900MPa.
[0038] In the anti-biological attachment material provided by the present invention, the content of the copper ion fiber in the preparation raw material can be specifically 5 parts by weight, 5.5 parts by weight, 6 parts by weight, 6.5 parts by weight, 7 parts by weight, 7.5 parts by weight, 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 9.5 parts by weight, 10 parts by weight, 10.5 parts by weight, 11 parts by weight, 11.5 parts by weight, 12 parts by weight, 12.5 parts by weight, 13 parts by weight, 13.5 parts by weight, 14 parts by weight, 14.5 parts by weight or 15 parts by weight.
[0039] In the anti-biological attachment material provided by the present invention, the auxiliary agent preferably includes one or more of a coupling agent, a dispersant, an antioxidant and a weathering agent; the content of the auxiliary agent in the preparation raw material can specifically be 0.6 weight parts, 0.7 weight parts, 0.8 weight parts, 0.9 weight parts, 1 weight part, 1.1 weight parts, 1.2 weight parts, 1.3 weight parts, 1.4 weight parts, 1.5 weight parts, 1.6 weight parts, 1.7 weight parts, 1.8 weight parts, 1.9 weight parts, 2 weight parts, 2.1 weight parts, 2.2 weight parts, 2.3 weight parts, 2.4 weight parts, 2.5 weight parts, 2.6 weight parts, 2.7 weight parts, 2.8 weight parts, 2.9 weight parts, 3 weight parts, 3.1 weight parts, 3.2 weight parts, 3.3 weight parts, 3.4 weight parts, 3.5 weight parts, 3.6 weight parts, 3.7 weight parts, 3.8 weight parts, 3.9 weight parts or 4 weight parts.
[0040] In the anti-biological attachment material provided by the present invention, the coupling agent is a plastic additive, also known as a surface modifier, which improves the interface performance between synthetic resin and inorganic filler or reinforcing material in plastic compounding. It can reduce the viscosity of synthetic resin melt during plastic processing and improve the dispersion of filler to improve processing performance. In the present invention, the coupling agent is preferably a silane coupling agent, more preferably silane coupling agent KH550.
[0041] In the anti-biological attachment material provided by the present invention, the content of the coupling agent in the preparation raw material is preferably 0.2 to 1.0 parts by weight, specifically 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight, 0.5 parts by weight, 0.55 parts by weight, 0.6 parts by weight, 0.65 parts by weight, 0.7 parts by weight, 0.75 parts by weight, 0.8 parts by weight, 0.85 parts by weight, 0.9 parts by weight, 0.95 parts by weight or 1 part by weight.
[0042] In the anti-biological attachment material provided by the present invention, the function of the dispersant is to reduce the friction between materials and between materials and processing equipment surfaces during plastic processing, thereby reducing the flow resistance and viscosity of the melt, improving the fluidity of the melt and the dispersant, and avoiding the adhesion of the melt to the melt and the melt to the equipment. In the present invention, the dispersant is preferably polyethylene wax and / or zinc stearate; the number average molecular weight of the polyethylene wax is preferably 2000-8000, more preferably 4000; the softening point of the polyethylene wax is preferably 100-110°C, more preferably 105°C.
[0043] In the anti-biological attachment material provided by the present invention, the content of the dispersant in the preparation raw material is preferably 0.2 to 2.0 parts by weight, specifically 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight, 1 part by weight, 1.1 parts by weight, 1.2 parts by weight, 1.3 parts by weight, 1.4 parts by weight, 1.5 parts by weight, 1.6 parts by weight, 1.7 parts by weight, 1.8 parts by weight, 1.9 parts by weight or 2 parts by weight.
[0044] In the anti-biological attachment material provided by the present invention, the antioxidant is preferably one or more of antioxidant 1010, antioxidant 1076 and antioxidant 168; in certain embodiments provided by the present invention, the antioxidant is preferably antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 and antioxidant 168 is preferably (1-3):(1-3), more preferably (2-3):(2-3), specifically 3:2 or 2:3; in certain embodiments provided by the present invention, the antioxidant is preferably antioxidant 1076 and antioxidant 168, and the mass ratio of antioxidant 1076 and antioxidant 168 is preferably 1:(0.5-5), more preferably 1:(1-2).
[0045] In the anti-biological attachment material provided by the present invention, the content of the antioxidant in the preparation raw material is preferably 0.1 to 0.5 parts by weight, specifically 0.1 parts by weight, 0.15 parts by weight, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight or 0.5 parts by weight.
[0046] In the anti-biological attachment material provided by the present invention, the weathering agent is preferably one or more of weathering agent 770, weathering agent 944 and weathering agent UV-P; in certain embodiments provided by the present invention, the weathering agent is preferably weathering agent 944 and weathering agent UV-P, and the mass ratio of weathering agent 944 and weathering agent UV-P is preferably (1-3):(1-3), specifically 1:1, 3:2 or 2:3; in certain embodiments provided by the present invention, the weathering agent is preferably weathering agent 770 and weathering agent UV-P, and the mass ratio of weathering agent 770 and weathering agent UV-P is preferably (1-3):1, more preferably 2:1.
[0047] In the anti-biological attachment material provided by the present invention, the content of the weathering agent in the preparation raw material is preferably 0.1 to 0.5 parts by weight, specifically 0.1 parts by weight, 0.15 parts by weight, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight or 0.5 parts by weight.
[0048] The present invention also provides a method for preparing the anti-biological attachment material described in the above technical solution, comprising the following steps:
[0049] The prepared raw materials are melt-blended and extruded to obtain the anti-biological attachment material.
[0050] In the preparation method provided by the present invention, the specific preparation process of the anti-biological attachment material preferably includes:
[0051] a) mixing polyolefin thermoplastic elastomer, nano zinc oxide, 2-(methoxycarbamoyl)benzimidazole, zinc pyrithione, hydrophobic white carbon black, coupling agent, dispersant, antioxidant and weathering agent, extruding and pelletizing to obtain a functional masterbatch;
[0052] b) melt-blending and extruding the functional masterbatch, high-density polyethylene and copper ion fiber to obtain an anti-biological attachment material.
[0053] In the preparation method provided by the present invention, in step a), the banburying is preferably carried out in an internal mixer; the temperature of the banburying is preferably 150-230°C, specifically 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C or 230°C; the speed of the banburying is preferably 120-200rpm, specifically 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm or 200rpm; the time of the banburying is preferably 30-60min, specifically 30min, 35min, 40min, 45min, 50min, 55min or 60min; and the pelletizing method is preferably underwater pelletizing.
[0054] In the preparation method provided by the present invention, in step b), the melt blending extrusion is preferably carried out in an extruder; the extrusion speed of the extruder is preferably 30-60 rpm, specifically 30 rpm, 35 rpm, 40 rpm, 45 rpm, 50 rpm, 55 rpm or 60 rpm; the temperature of zone 1 of the extruder is preferably 150-200°C, specifically 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C or 200°C; the temperatures of other zones and the die of the extruder are preferably 180-230°C, specifically 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C or 230°C.
[0055] In the preparation method provided by the present invention, after the raw materials are melt-blended and extruded, granulation is preferably performed to obtain anti-biological attachment granular materials.
[0056] The present invention also provides an anti-biological attachment floating body, the surface material of the anti-biological attachment floating body is the anti-biological attachment material described in the above technical solution.
[0057] The technical solution provided by the present invention optimizes the raw material formula of polymer materials to obtain a material with good anti-biological adhesion ability, which can effectively prevent biological adhesion for a long time, and overcomes the problems of poor anti-biological adhesion and short validity period of existing materials. When the material is used as a floating material, it can effectively reduce the manual cleaning of the floating surface, thereby avoiding the negative impact of frequent manual cleaning on the floating body, and has good application prospects in the field of floating materials for offshore photovoltaic power generation.
[0058] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.
[0059] Example 1
[0060] This embodiment prepares an anti-biological attachment floating material, including the following raw materials in parts by weight:
[0061] High-density polyethylene (melt flow rate (190°C, load 2.16kg) is 15g / 10min, environmental stress cracking time F 50 65.0 parts of polyolefin thermoplastic elastomer (Mooney viscosity ML (1+4) 121°C is 18MU, tear strength 30 kN / m, glass transition temperature -59°C), 3.0 parts of nano zinc oxide (particle size 10 nm), 2.0 parts of 2-(methoxycarbamoyl) benzimidazole, 2.0 parts of zinc pyrithione, and hydrophobic white carbon black (specific surface area 400 m 2 / g, water contact angle 151°) 2.0 parts, silane coupling agent KH550 0.5 parts, dispersant polyethylene wax (number average molecular weight 4000, softening point 105°C) 0.5 parts, antioxidant 1010 0.3 parts, antioxidant 168 0.2 parts, weathering agent 944 0.2 parts, weathering agent UV-P 0.3 parts, copper ion fiber (polyetheretherketone matrix, copper content 50000ppm, diameter 5μm, aspect ratio 200, tensile strength 720MPa) 9.0 parts.
[0062] The specific preparation steps are as follows:
[0063] a) placing a polyolefin thermoplastic elastomer in an internal mixer for melting and plasticization, and then adding nano zinc oxide, 2-(methoxycarbamoyl)benzimidazole, zinc pyrithione, hydrophobic white carbon black, coupling agent, dispersant, antioxidant and weathering agent according to the proportion, the internal mixer temperature is 180° C., the internal mixer speed is 150 rpm, the internal mixer time is 45 min, and after the internal mixer is evenly mixed, it is extruded and pelletized underwater to obtain a functional masterbatch;
[0064] b) The functional masterbatch obtained in step a) is melt-blended and extruded with high-density polyethylene and copper ion fiber in an extruder, the extruder speed is 45 rpm, the temperature of zone 1 is 180° C., and the temperatures of other zones and the die are all 210° C. After extrusion, granulation is performed to obtain an anti-biological attachment floating body material.
[0065] Example 2
[0066] This embodiment prepares an anti-biological attachment floating material, including the following raw materials in parts by weight:
[0067] High-density polyethylene (melt flow rate (190°C, load 2.16kg) is 15g / 10min, environmental stress cracking time F 50 60.0 parts of polyolefin thermoplastic elastomer (Mooney viscosity ML (1+4) 121°C is 18MU, tear strength 30 kN / m, glass transition temperature -59°C), 2.0 parts of nano zinc oxide (particle size 10 nm), 3.0 parts of 2-(methoxycarbamoyl) benzimidazole, 3.0 parts of zinc pyrithione, and hydrophobic white carbon black (specific surface area 400 m 2 / g, water contact angle 151°) 3.0 parts, silane coupling agent KH550 1.0 parts, dispersant polyethylene wax (number average molecular weight 4000, softening point 105°C) 2.0 parts, antioxidant 1010 0.2 parts, antioxidant 168 0.3 parts, weathering agent 944 0.3 parts, weathering agent UV-P 0.2 parts, copper ion fiber (polyetheretherketone matrix, copper content 50000ppm, diameter 0.5μm, aspect ratio 150, tensile strength 820MPa) 15.0 parts.
[0068] The specific preparation steps are as follows:
[0069] a) placing a polyolefin thermoplastic elastomer in an internal mixer for melting and plasticization, and then adding nano zinc oxide, 2-(methoxycarbamoyl)benzimidazole, zinc pyrithione, hydrophobic white carbon black, coupling agent, dispersant, antioxidant and weathering agent according to the proportion, the internal mixer temperature is 230° C., the internal mixer speed is 200 rpm, the internal mixer time is 60 min, and after the internal mixer is evenly mixed, it is extruded and pelletized underwater to obtain a functional masterbatch;
[0070] b) The functional masterbatch obtained in step a) is melt-blended and extruded with high-density polyethylene and copper ion fiber in an extruder, the extruder speed is 30 rpm, the temperature of zone 1 is 200° C., the temperatures of other zones and the die are all 230° C., and granulation is performed after extrusion to obtain an anti-biological attachment floating body material.
[0071] Example 3
[0072] This embodiment prepares an anti-biological attachment floating material, including the following raw materials in parts by weight:
[0073] High-density polyethylene (melt flow rate (190°C, load 2.16kg) is 10g / 10min, environmental stress cracking time F 50 60.0 parts of polyolefin thermoplastic elastomer (Mooney viscosity ML (1+4) 121°C is 18MU, tear strength 30 kN / m, glass transition temperature -59°C), 0.5 parts of nano zinc oxide (particle size 10 nm), 0.5 parts of 2-(methoxycarbamoyl)benzimidazole, 0.5 parts of zinc pyrithione, hydrophobic white carbon black (specific surface area 400 m 2 / g, water contact angle 151°) 0.5 parts, silane coupling agent KH550 0.2 parts, dispersant zinc stearate 0.4 parts, antioxidant 1076 0.1 parts, antioxidant 168 0.1 parts, weathering agent 944 0.1 parts, weathering agent UV-P 0.1 parts, copper ion fiber (polyetheretherketone matrix, copper content 50000ppm, diameter 1μm, aspect ratio 150, tensile strength 800MPa) 12.0 parts.
[0074] The specific preparation steps are as follows:
[0075] a) placing a polyolefin thermoplastic elastomer in an internal mixer for melting and plasticization, and then adding nano zinc oxide, 2-(methoxycarbamoyl)benzimidazole, zinc pyrithione, hydrophobic white carbon black, coupling agent, dispersant, antioxidant and weathering agent according to the proportion, the internal mixer temperature is 180° C., the internal mixer speed is 150 rpm, the internal mixer time is 45 min, and after the internal mixer is evenly mixed, it is extruded and pelletized underwater to obtain a functional masterbatch;
[0076] b) The functional masterbatch obtained in step a) is melt-blended and extruded with high-density polyethylene and copper ion fiber in an extruder, the extruder speed is 60 rpm, the temperature of zone 1 is 200° C., and the temperatures of other zones and the die are all 230° C. After extrusion, granulation is performed to obtain an anti-biological attachment floating body material.
[0077] Example 4
[0078] This embodiment prepares an anti-biological attachment floating material, including the following raw materials in parts by weight:
[0079] High-density polyethylene (melt flow rate (190°C, load 2.16kg) is 20g / 10min, environmental stress cracking time F 5075.0 parts (50°C, 10% Igepal) for 5000h), 10.0 parts of polyolefin thermoplastic elastomer (Mooney viscosity ML (1+4) 121°C is 18MU, tear strength 30 kN / m, glass transition temperature -59°C), 0.5 parts of nano zinc oxide (particle size 10 nm), 0.5 parts of 2-(methoxycarbamoyl)benzimidazole, 0.5 parts of zinc pyrithione, hydrophobic white carbon black (specific surface area 400m 2 / g, water contact angle 151°) 0.5 parts, silane coupling agent KH550 0.2 parts, dispersant zinc stearate 0.2 parts, antioxidant 1076 0.1 parts, antioxidant 168 0.2 parts, weathering agent 7700 0.2 parts, weathering agent UV-P 0.1 parts, copper ion fiber (polyetheretherketone matrix, copper content 50000ppm, diameter 2μm, aspect ratio 150, tensile strength 780MPa) 12.0 parts.
[0080] The specific preparation steps are as follows:
[0081] a) placing a polyolefin thermoplastic elastomer in an internal mixer for melting and plasticization, and then adding nano zinc oxide, 2-(methoxycarbamoyl)benzimidazole, zinc pyrithione, hydrophobic white carbon black, coupling agent, dispersant, antioxidant and weathering agent according to the proportion, wherein the internal mixing temperature is 200° C., the internal mixing speed is 180 rpm, and the internal mixing time is 45 min. After the internal mixing is uniform, the functional masterbatch is obtained by extrusion and underwater pelletization;
[0082] b) The functional masterbatch obtained in step a) is melt-blended and extruded with high-density polyethylene and copper ion fiber in an extruder, the extruder speed is 45 rpm, the temperature of zone 1 is 190° C., and the temperatures of other zones and the die are all 220° C. After extrusion, granulation is performed to obtain an anti-biological attachment floating body material.
[0083] Example 5
[0084] This embodiment prepares an anti-biological attachment floating material, including the following raw materials in parts by weight:
[0085] High-density polyethylene (melt flow rate (190°C, load 2.16kg) is 20g / 10min, environmental stress cracking time F 50 60.9 parts of polyolefin thermoplastic elastomer (Mooney viscosity ML (1+4) 121°C is 18MU, tear strength 30 kN / m, glass transition temperature -59°C), 25.0 parts of nano zinc oxide (particle size 10 nm), 2.5 parts of 2-(methoxycarbamoyl)benzimidazole, 2.5 parts of zinc pyrithione, hydrophobic white carbon black (specific surface area 400m 2 / g, water contact angle 151°) 2.5 parts, silane coupling agent KH5500 0.2 parts, dispersant polyethylene wax (number average molecular weight 4000, softening point 105°C) 0.2 parts, antioxidant 1680.1 parts, weathering agent 9440.1 parts, copper ion fiber (polyetheretherketone matrix, copper content 50000ppm, diameter 10μm, aspect ratio 100, tensile strength 660MPa) 5.0 parts.
[0086] The specific preparation steps are as follows:
[0087] a) placing a polyolefin thermoplastic elastomer in an internal mixer for melting and plasticization, and then adding nano zinc oxide, 2-(methoxycarbamoyl)benzimidazole, zinc pyrithione, hydrophobic white carbon black, coupling agent, dispersant, antioxidant and weathering agent according to the proportion, the internal mixer temperature is 150° C., the internal mixer speed is 120 rpm, the internal mixer time is 30 min, and after the internal mixer is evenly mixed, it is extruded and pelletized underwater to obtain a functional masterbatch;
[0088] b) The functional masterbatch obtained in step a) is melt-blended and extruded with high-density polyethylene and copper ion fiber in an extruder, the extruder speed is 60 rpm, the temperature of zone 1 is 150° C., and the temperatures of other zones and the die are all 180° C. After extrusion, granulation is performed to obtain an anti-biological attachment floating material.
[0089] Comparative Example 1
[0090] This comparative example prepares a floating material, comprising the following raw materials in parts by weight:
[0091] High-density polyethylene (melt flow rate (190°C, load 2.16kg) is 15g / 10min, environmental stress cracking time F 50 (50°C, 10% Igepal) for 5000h) 75.0 parts, polyolefin thermoplastic elastomer (Mooney viscosity ML (1+4) 121°C is 18MU, tear strength 30 kN / m, glass transition temperature -59°C) 21.0 parts, silane coupling agent KH550 1.0 parts, dispersant polyethylene wax (number average molecular weight 4000, softening point 105°C) 2.0 parts, antioxidant 1010 0.2 parts, antioxidant 168 0.3 parts, weathering agent 944 0.3 parts, weathering agent UV-P 0.2 parts.
[0092] The specific preparation steps are as follows:
[0093] a) putting a polyolefin thermoplastic elastomer into an internal mixer for melting and plasticizing, and then adding a coupling agent, a dispersant, an antioxidant and a weathering agent according to a proportion, wherein the internal mixing temperature of the internal mixer is 180° C., the internal mixing speed is 150 rpm, and the internal mixing time is 45 min. After the internal mixing is uniform, the mixture is extruded and pelletized underwater to obtain a functional masterbatch;
[0094] b) The functional masterbatch obtained in step a) is melt-blended and extruded with high-density polyethylene in an extruder. The extruder speed is 60 rpm, the temperature of zone 1 is 200° C., and the temperatures of other zones and the die are all 230° C. After extrusion, granulation is performed to obtain a floating material.
[0095] Comparative Example 2
[0096] This comparative example prepares an anti-biological attachment floating material, comprising the following raw materials in parts by weight:
[0097] High-density polyethylene (melt flow rate (190°C, load 2.16kg) is 15g / 10min, environmental stress cracking time F 50 (50°C, 10% Igepal) for 5000h) 69.0 parts, polyolefin thermoplastic elastomer (Mooney viscosity ML (1+4) 121°C is 18MU, tear strength 30 kN / m, glass transition temperature -59°C) 10.0 parts, nano zinc oxide (particle size 10nm) 2.0 parts, silane coupling agent KH550 1.0 parts, dispersant polyethylene wax (number average molecular weight 4000, softening point 105°C) 2.0 parts, antioxidant 1010 0.2 parts, antioxidant 168 0.3 parts, weathering agent 944 0.3 parts, weathering agent UV-P 0.2 parts, copper ion fiber (polyetheretherketone matrix, copper content 50000ppm, diameter 0.5μm, aspect ratio 150, tensile strength 820MPa) 15.0 parts.
[0098] The specific preparation steps are as follows:
[0099] a) putting a polyolefin thermoplastic elastomer into an internal mixer for melting and plasticization, and then adding nano zinc oxide, coupling agent, dispersant, antioxidant and weathering agent according to the proportion, the internal mixer temperature is 230° C., the internal mixer speed is 200 rpm, the internal mixer time is 60 min, and after the internal mixer is evenly mixed, it is extruded and pelletized underwater to obtain a functional masterbatch;
[0100] b) The functional masterbatch obtained in step a) is melt-blended and extruded with high-density polyethylene and copper ion fiber in an extruder, the extruder speed is 30 rpm, the temperature of zone 1 is 200° C., the temperatures of other zones and the die are all 230° C., and granulation is performed after extrusion to obtain an anti-biological attachment floating body material.
[0101] Comparative Example 3
[0102] This comparative example prepares an anti-biological attachment floating material, comprising the following raw materials in parts by weight:
[0103] High-density polyethylene (melt flow rate (190°C, load 2.16kg) is 15g / 10min, environmental stress cracking time F 5075.0 parts (50°C, 10% Igepal) for 5000h), 12.0 parts of polyolefin thermoplastic elastomer (Mooney viscosity ML (1+4) 121°C is 18MU, tear strength 30 kN / m, glass transition temperature -59°C), 3.0 parts of 2-(methoxycarbamoyl)benzimidazole, 3.0 parts of zinc pyrithione, hydrophobic white carbon black (specific surface area 400m 2 / g, water contact angle 151°) 3.0 parts, silane coupling agent KH550 1.0 parts, dispersant polyethylene wax (number average molecular weight 4000, softening point 105°C) 2.0 parts, antioxidant 1010 0.2 parts, antioxidant 168 0.3 parts, weathering agent 944 0.3 parts, weathering agent UV-P 0.2 parts.
[0104] The specific preparation steps are as follows:
[0105] a) placing a polyolefin thermoplastic elastomer in an internal mixer for melting and plasticization, and then adding 2-(methoxycarbamoyl)benzimidazole, zinc pyrithione, hydrophobic white carbon black, coupling agent, dispersant, antioxidant and weathering agent according to the proportion, wherein the internal mixer has an internal mixing temperature of 230° C., a internal mixing speed of 200 rpm and a internal mixing time of 60 min, extruding after uniform internal mixing, and underwater pelletizing to obtain a functional masterbatch;
[0106] b) The functional masterbatch obtained in step a) is melt-blended and extruded with high-density polyethylene in an extruder, the extruder speed is 30 rpm, the temperature of zone 1 is 200° C., and the temperatures of other zones and the die are all 230° C. After extrusion, granulation is performed to obtain an anti-biological attachment floating body material.
[0107] Performance Testing:
[0108] 1. Melt flow rate: refer to GB / T 3682.1-2018, test temperature 190℃, weight 2.16kg;
[0109] 2. Bending modulus: refer to GB / T 9341-2008, bending spline thickness 4mm, span 64mm, deflection 6mm;
[0110] 3. Weight ratio of attachments: The above-mentioned floating materials are sampled into floating bodies, and field tests are carried out in the ocean. The attachments on the surface of the floating samples are collected after 12 months, and the weight in the dry state is measured. The ratio of the weight of the attachments to the weight of the floating bodies is the weight ratio of attachments.
[0111] 4. Anti-fouling validity period: The above-mentioned floating materials are sampled into floating bodies and tested in the ocean. The period when the area of marine organism attachment on the surface of the floating body is less than 10% is the anti-fouling validity period.
[0112] The performance of the floating materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were tested according to the above performance testing method. The results are shown in Table 1:
[0113] Table 1 Performance test data of the floating material obtained in Examples 1 to 5 and Comparative Examples 1 to 3
[0114]
[0115] It can be seen from Table 1 that compared with Comparative Examples 1 to 3, the anti-biological attachment floating materials of Examples 1 to 5 are added with a variety of organic antibacterial components and a variety of inorganic antibacterial components at the same time. The introduction of nano zinc oxide and copper ion fiber solves the problem of short anti-biological attachment time when 2-(methoxycarbamoyl)benzimidazole and zinc pyrithione are added separately, and improves the long-term anti-biological attachment performance of the floating body. At the same time, the high strength of the copper ion fiber gives the floating material excellent rigidity. The anti-biological attachment floating materials provided by Examples 1 to 5 have excellent properties, can effectively reduce the manual cleaning of the floating surface, thereby avoiding the negative impact of frequent manual cleaning on the floating body, can meet the use requirements of offshore photovoltaic power generation, and have good application prospects in the field of floating materials for offshore photovoltaic power generation.
[0116] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An anti-biological attachment material, characterized in that: The raw materials for preparing the anti-biological attachment material include, by weight: The copper content of the copper ion fiber is 5000-50000 ppm.
2. The anti-biological attachment material according to claim 1, characterized in that: The polymer base material includes high-density polyethylene and polyolefin thermoplastic elastomer.
3. The anti-biological attachment material according to claim 2, characterized in that: The melt flow rate of the high-density polyethylene at 190°C and 2.16kg load is 10-20g / 10min; the environmental stress cracking time F of the high-density polyethylene at 50°C and 10% Igepal is 50 is ≥2000h; the Mooney viscosity ML(1+4) 121°C of the polyolefin thermoplastic elastomer is ≤20MU; the tear strength of the polyolefin thermoplastic elastomer is ≥25kN / m; and the glass transition temperature of the polyolefin thermoplastic elastomer is ≤-55°C.
4. The anti-biological attachment material according to claim 1, characterized in that: The particle size of the nano zinc oxide is 5 to 20 nm.
5. The anti-biological attachment material according to claim 1, characterized in that: The specific surface area of the hydrophobic white carbon black is 300 to 500 m 2 / g; the water contact angle of the hydrophobic silica is ≥150°.
6. The anti-biological attachment material according to claim 1, characterized in that: The base material of the copper ion fiber is one or more of polyethylene terephthalate, polyamide and polyetheretherketone; the diameter of the copper ion fiber is 0.5-10 μm; and the aspect ratio of the copper ion fiber is ≥100.
7. The anti-biological attachment material according to claim 1, characterized in that: The auxiliary agent includes one or more of a coupling agent, a dispersant, an antioxidant and a weathering agent.
8. The anti-biological attachment material according to claim 1, characterized in that: In parts by weight, the raw materials for preparation include:
9. A method for preparing the anti-biological attachment material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The prepared raw materials are melt-blended and extruded to obtain the anti-biological attachment material.
10. An anti-biological attachment floating body, characterized in that: The surface material of the anti-biological attachment floating body is the anti-biological attachment material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Long-acting antibacterial and mildew-proof silicone adhesive and preparation method thereof
CN103773308A
High-strength aging-resistant polyethylene composite material for photovoltaic floating bodies and preparation method thereof
CN111253661A